Evaluation of an Online Learning Concept for Nursing Students in Caring for Patients with Dementia: Results of a Questionnaire Survey - Adina Dreier-Wolfgramm; Anja Teubner; Katrin Kern (MDPI AG, 2023)
Background: Nurses have key roles in caring for patients with dementia. To prepare them for demand-oriented nursing care, there is a need for education. An online course with a focus on healthcare needs assessment was designed. Methods: A quantitative study with a qualitative component using questionnaire-based interviews was implemented. The recruitment of students used the following inclusion criteria: (a) second-year students, and (b) absent from less than three lectures. Overall, n = 48 met the inclusion criteria. Twenty-eight students participated. Quantitative data were analyzed using descriptive statistics. Qualitative data were evaluated using Kuckartz's content analysis with the software MAXQDA. Results: Nursing students judged the overall course structure as very good (M 1.36, SD 0.48). The learning aims were clearly defined (M 1.61, SD 0.68) and the learning content was adequately demonstrated (M 1.68, SD 0.67). The exercise on geriatric assessment promoted the internal learning process (M 1.67, SD 1.00). The online simulation training made the lectures' contents easier to understand (M 1.86, SD 0.89). Correlations were determined, among others, between the course structure and the clear definitions of the learning aims (rSp 0.566, p = 0.002). Conclusions: The study describes the feasibility of the online course. To identify the impact on patients' health and caregivers' lives, further studies are needed.